Risk of skin cancer in new users of thiazides and thiazide‐like diuretics: a cohort study using an active comparator group. (28th April 2021) - Schneider, R.; Reinau, D.; Stoffel, S.; Jick, S.S.; Meier, C.R.; Spoendlin, J.
Summary: Background: Case–control studies report a dose‐dependent increased risk of skin cancer in users of hydrochlorothiazide (HCTZ) vs. nonusers. The degree to which other thiazides and thiazide‐like diuretics (TZs) are associated with skin cancer is less certain. Objectives: To assess the risk of skin cancer in new users of different TZs compared with new users of calcium channel blockers (CCBs). Methods: We conducted a cohort study using a UK primary‐care database (1998–2017), including 271 154 new TZ users [87·6% bendroflumethiazide (BFT), 5·8% indapamide and 3·6% HCTZ] and 275 263 CCB users. The outcomes were basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and cutaneous malignant melanoma (CMM). We estimated incidence rates (IRs) and IR ratios (IRRs) in short‐term (< 20 prescriptions) and long‐term (≥ 20 prescriptions) users of TZs and CCBs using negative binomial regression, and calculated rate differences (RDs) for selected results. We used fine stratification on the propensity score (PS) to control for 23 baseline covariates. Results: Long‐term use of HCTZ increased absolute and relative risks of SCC [PS‐weighted IRR 1·95; 95% confidence interval (CI) 1·87–2·02; RD per 100 000 person‐years 87.4], but not of BCC or CMM. Long‐term use of indapamide was associated with an increased incidence of CMM (IRR 1·43; 95% CI 1·35–1·50). BFT was not meaningfully associated with the risk of any type of skin cancer. Conclusions: Our results corroborate the previously reported increased risk of SCC (but not of BCC or CMM) for long‐term use of HCTZ. BFT may be a safer alternative for patients at increased risk of skin cancer. Abstract : What is already known about this topic? Thiazides and thiazide‐like diuretics (TZs) hold photosensitizing properties. Two Danish case–control studies reported a strongly increased risk of skin cancer [fourfold increase for squamous cell carcinoma (SCC), and moderate increase for basal cell carcinoma (BCC) and cutaneous malignant melanoma (CMM)] in long‐term users of hydrochlorothiazide (HCTZ) compared with nonusers. The degree to which other TZs are associated with skin cancer is less certain. What does this study add? We report relative and absolute incidences of skin cancers in association with use of different TZs and other antihypertensives. In long‐term HCTZ users, we observed a dose‐dependent twofold risk increase of SCC (0·8%) when compared with long‐term calcium channel blocker users (0·3%), but not of BCC or CMM; this risk increase seems to be specific to HCTZ. Long‐term use of bendroflumethiazide appears to be safer than other TZs with regard to skin cancer risk. Linked Comment:  L.M. Hollestein and S. Arnspang Pedersen. Br J Dermatol 2021; 185 :244–245 . Plain language summary available online